A proposal of a methodology for teaching formative Investigation in institution of higher learning. - Enríquez Montenegro, César Armando; Arcos Ponce, Georgina Guadalupe; Mina Ortega, Jorge Iván (SATHIRI, 2019)
One of the greatest problems plaguing Ecuadorian universities is undoubtedly the teaching of formative research. To this end, disciplinary, interdisciplinary, trans-disciplinary, professional research knowledge and communicative skills were concrete necessities for the development of the professional and academic profile of student of higher education and should be organized into subjects, courses or their equivalents. In turn, these components are organized throughout the learning process through the units of curricular organization, which is part of the unit of degree in the curricula of the University of Ecuador. The purpose of this research is to develop a methodology for the teaching learning process of formative scientific research. It is a research of descriptive level, since it allowed us to characterize a fact in order to establish its structure. It is in this field that information was made directly without manipulating or controlling any variable and was applied because it was intended to proffer solution to a problem of higher educational context of the Polytechnic University of Carchi. As a methodology for the construction of a matrix according to matrixes published in the Sathiri magazine of 2015, the new matrix was tested from October 2015 to August 2017, both in the careers of Tourism, IT and Food Technology. The major results were: the development of a matrix as a didactic resource for teaching-learning process of a formative research, the learning of the formative research in students through logical reasoning and above all, to understand the coherence of investigative process and to look into scientific research as a systematic and systemic process to exterminate investigative fears.